PENGARUH KOMPETENSI, BEBAN KERJA, KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU KELOMPOK BERMAIN KECAMATAN LASEM KABUPATEN REMBANG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this research problem stems from the crucial role of Playgroup (Kelompok Bermain - KB) teacher performance in Lasem Sub-district, Rembang Regency, in guaranteeing the quality of early childhood education, which is demanded to provide engaging learning that encourages child exploration. This study aims to determine the extent of the partial effect of competence, workload, compensation, and work environment on teacher performance in Lasem Sub-district, Rembang Regency, with teacher performance serving as the dependent variable and competence, workload, compensation, and work environment as the independent variables. The research method utilized a quantitative approach, sourcing data from primary data. Data collection was carried out by distributing closed questionnaires using a Likert scale. The sample consisted of 125 Playgroup teachers in Lasem Sub-district, Rembang Regency. This study employed the multiple linear regression data analysis technique with a significance level set at < 0,05. The research findings indicate that: (1) competence has a positive and significant effect on teacher performance, with a significance value of 0,021 < 0,05 (positive direction). (2) workload also has a positive and significant effect on teacher performance, with a significance value of 0,005 < 0,05 (positive direction). Conversely, (3) compensation has a negative and non-significant effect on teacher performance, with a significance value of 0,294 > 0,05 (negative direction). (4) work environment has a positive but non-significant effect on teacher performance, with a significance value of 0,394 > 0,05 (positive direction). It can therefore be concluded that in early childhood education in Lasem Sub-district, Rembang Regency, compensation and work environment do not have a significant impact on teacher performance.